EU Enlargement and the Future of the Welfare State - Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2000)
The eastern expansion of the EU resembles German unification in its mometousness. Whereas the latter led to a 26% increase in the population of the Federal Republic, the former will increase the population of the EU by 28% if all ten entry aspirants are accepted. A special problem will be posed by migration. In view of the existing wage differences between eastern and western Eurpean countries, a massive westward migration can be expected after EU expansion. A temporary east-to-west migration up to the time that the eastern countries have created an efficient capital stock makes economic sense if it is driven by wage differences and meets with a flexible labour market. Migration does not make economic sense, however, if, and to the extent to which, it is induced by the current social assistance systems. Moreover, welfare-motivated migration would create competition among western European states to frighten off potential migrants, which would lead to an erosion of the traditional social welfare state. If the EU plan incorporated a limitation of the free movement of labour, the beneficial migration would also be stopped. A better solution would be to limit access to the western social systems, at least for a transitional period in order to filter out migration induced by differing social standards. An EU-wide application of the home-country principle in the granting of social benefits would achieve this goal.
Keywords: 330